Women of the European Union : the politics of work and daily life - Garcia i Ramon, Maria Dolors; Monk, Janice J. (Routledge international studies of women and place., 1996)
Women of the European Union challenges gender- blind assessments of the economic and social aspects of the Union's policies to examine the real implications of Union for the diversity of women in the Member States.